ANALISIS PENGEMBANGAN DESA WISATA “NGEBEL ADVENTURE PARK” - Dwi Lestari; Mansur Azis (Institut Agama Islam Negeri Ponorogo, 2022)
Development is very important to do in a tourist attraction because it is a process of change from something that has been good to be even better. Without the development of a tourist attraction, there will be no developments and changes that occur to the object. With the development of Ngebel Adventure Park tourism properly, it is expected to create jobs. Business field for the community and can drive the economy for the surrounding community, especially Ngebel Village, Ngebel District, Ponorogo Regency. The main purpose of this study was to analyze how the development was carried out in the